Perancangan Mesin pengupas Kulit Telur Burung Puyuh Semi-Otomatis Berkapasitas 240 Butir / Jam - S, Rianto; Siregar, Amru; Tanjung, Faisal Amri (Universitas Medan Area, 2022)
The motivation behind this plan is to speed up the stripping of quail egg shells, quail eggs are typically handled with different types of food, subsequently requiring a stripping cycle. The timeframe for stripping quail egg shells by manual is a normal of 10 seconds/thing, on the off chance that in huge amounts a peeler is required. From these issues the creator made a